2005
DOI: 10.1002/da.20065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age of onset on clinical features in obsessive-compulsive disorder

Abstract: We compared early-onset and late-onset obsessive-compulsive disorder (OCD) patients in terms of demographic and clinical features. One hundred sixteen outpatients whose primary diagnosis was OCD according to DSM-IV diagnostic criteria were recruited. Early-onset (n=50) and late-onset (n=66) OCD groups were compared with respect to demographic variables and scores obtained on various scales. A male gender predominance was found in early-onset OCD group. Symmetry/exactness obsessions, religious obsessions, hoard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
4
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 25 publications
5
46
4
5
Order By: Relevance
“…There is evidence that religiosity can influence the way in which a person experiences OCD (Greenberg and Witztum 1994;Tukel et al 2005), as religious OCD symptoms have been found to occur earlier in the course of OCD than other OCD symptoms (Tukel et al 2005;Hasler et al 2007) and are more resistant to cognitive behavioural therapy (CBT; Ferrao et al 2006;Alonso et al 2001;Mataix-Cols et al 2002). Some studies conducted in Middle Eastern countries such as Saudi Arabia, Iran, and Israel have found religious obsessions to be more common than contamination obsessions (Ghassemzadeh et al 2005, Ghassemzadeh et al 2005Greenberg 1984) and purity is closely associated with some cultural practices of religions such as Islam (e.g., (Al-Solaim and Loewenthal 2011;Ghassemzadeh et al 2005;Shooka et al 1998)).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that religiosity can influence the way in which a person experiences OCD (Greenberg and Witztum 1994;Tukel et al 2005), as religious OCD symptoms have been found to occur earlier in the course of OCD than other OCD symptoms (Tukel et al 2005;Hasler et al 2007) and are more resistant to cognitive behavioural therapy (CBT; Ferrao et al 2006;Alonso et al 2001;Mataix-Cols et al 2002). Some studies conducted in Middle Eastern countries such as Saudi Arabia, Iran, and Israel have found religious obsessions to be more common than contamination obsessions (Ghassemzadeh et al 2005, Ghassemzadeh et al 2005Greenberg 1984) and purity is closely associated with some cultural practices of religions such as Islam (e.g., (Al-Solaim and Loewenthal 2011;Ghassemzadeh et al 2005;Shooka et al 1998)).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the DSM V separates hoarding compulsions into a new disorder, i.e., the 'Hoarding Disorder' . Some authors [4,9,[14][15][16] have distinguished between childhood-onset and adult-onset OCD. These authors suggest that childhood onset OCD signifies a phenomenologically and etiologically distinct subtype of OCD, bearing a close genetic connection to tic-disorders and probably sharing an analogous pathogenesis.…”
Section: Childhood Vs Adult Ocdmentioning
confidence: 99%
“…Obsessive compulsive disorder is a chronic disabling sickness characterized (7,8). Cleaning compulsions and washing are common in children (9,10). Very few studies have assessed the association between pollakiuria and obsessive-compulsive disorder (OCD) (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%